2009
DOI: 10.1103/physrevb.79.224501
|View full text |Cite
|
Sign up to set email alerts
|

Competition between different order parameters in a quasi-one-dimensional superconductor

Abstract: We show that, under rather general assumptions, the phase diagram of a quasi-one-dimensional repulsive Fermi system consists of two ordered phases: the density wave, spin or charge, and the superconductivity. It is demonstrated that the symmetry of the superconducting order parameter is a nonuniversal property sensitive to microscopic details of the model. Three potentially stable superconducting states are identified: they are triplet f-wave, singlet d x 2 −y 2-wave, and d xy -wave. The presence of multiple c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, a "universal" phase diagram 8,9 suggests the superconductivity is in close proximity to the density-wave and most probably originated from non-phonon pairing mechanism. However, the determination of the pairing symmetry for these compound was difficult due to the competition between several energetically close ordering parameters 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a "universal" phase diagram 8,9 suggests the superconductivity is in close proximity to the density-wave and most probably originated from non-phonon pairing mechanism. However, the determination of the pairing symmetry for these compound was difficult due to the competition between several energetically close ordering parameters 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the pairing mechanism is still far from an established settlement for (TMTSF) 2 X in spite of several theoretical studies. [3][4][5][6][7][8][9] Synchronous to the theoretical struggle, a number of experimental studies have been also made to clarify the superconducting pairing symmetry for (TMTSF) 2 ClO 4 . The superconducting transition temperature for (TMTSF) 2 (ClO 4 ) 1−x (ReO 4 ) x is suppressed by a tiny amount of nonmagnetic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…8 Afterward, several theoretical studies have suggested effective models with or without the anion ordering to discuss the pairing mechanism. [3][4][5][6][7]9 However, there has been no first-principles calculation taking account of the anion ordering. Here, we emphasize that a trustful band calculation resolves the effects of the anion ordering on the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…( 19) the Heaviside step function is denoted as θ(x). System of equations ( 18), (19) for the unknown variable k has solutions only when 0 < ω < ω sdw 1 , where…”
Section: B Evaluation Of the Susceptibility Tensormentioning
confidence: 99%